Human capital and optimal redistribution - Winfried Koeniger; Julien Prat (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
We characterize optimal redistribution in a dynastic family model with human capital. We show how a government can improve the trade-off between equality and incentives by changing the amount of observable human capital. We provide an intuitive decomposition for the wedge between human-capital investment in the laissez faire and the social optimum. This wedge differs from the wedge for bequests because human capital carries risk: its returns depend on the non-diversifiable risk of children's ability. Thus, human capital investment is encouraged more than bequests in the social optimum if human capital is a bad hedge for consumption risk.
urn:nbn:de:hebis:30:3-356112
Keywords: E24; H21; I22; J24; 330; human capital; optimal taxation